ANALISIS PEMANFAATAN DOLOMIT DALAM PAKAN TERHADAP PERIODE MOLTING UDANG VANAME (Litopenaeus vannamei) DI TAMBAK UNIKAL - Nur ’Aisyah; Muhamad Agus; Tri Yusufi Mardiana (Fakultas Perikanan Universitas Pekalongan, 2017)
Vaname shrimp (Litopenaeus vannamei) was kind of shrimp that cultivating by globally. Vaname shrimp has an euryhaline character or able to live on wide salinity. At low salinity watery, the availibility of minerals is too low. This research has to analized using dolomite as pellet for moulting period of vaname shrimp. This research was use sample survey method or field survey, and analyzing descriptively. The value of research shows that adding dolomite at vaname shrimp’s feed could help moulting proccess and growth faster. Growth data in pond 1 shows that MBW is 16,39 g with size 61 and pond 2 MBW is 13,7 g with size 72. Difference result in Mean Body Weight (MBW) is 2,69 g and size difference on 11. Water quality take effect on osmoregulation and metabolic rate.Keywords : Vaname shrimp, dolomite, moulting, growth, water quality